Efficacy of interleukin-17 inhibitors in psoriasis patients: a comparative non-randomized study - Arfenya E. Karamova; Anastasiia A. Vorontsova; Olga G. Artamonova (Vestnik Dermatologii i Venerologii, 2025)
Background. IL-17 blockers have expanded the possibilities of psoriasis therapy. Their high efficacy and safety profile have been demonstrated in phase I–III studies and in real-world clinical practice. No direct comparative studies of the efficacy of drugs of this class registered in the Russian Federation have been conducted.